Metagenomic analysis revealed the bioremediation mechanism of lead and cadmium contamination by modified biochar synergized with Bacillus cereus PSB-2 in phosphate mining wasteland - Zhang, Yuxin; Peng, Jun; Wang, Ziwei; Zhou, Fang; Yu, Junxia; Chi, Ruan; Xiao, Chunqiao (Frontiers in Microbiology, 2025)
IntroductionPhosphate mining wasteland is contaminated with heavy metals, such as lead (Pb) and cadmium (Cd), which pose significant environmental risks. Ecological restoration of these lands is crucial, but limited research has focused on the remediation of heavy metal-contaminated soils using modified biochar and functional microorganisms.MethodsIn this study, we investigated the bioremediation of phosphate mining wasteland soil using modified biochar in combination with the phosphate-solubilizing bacterium Bacillus cereus. The effects of this synergistic approach on soil nutrient content, heavy metal immobilization, and microbial community structure were assessed.Results and discussionThe results indicated that the available phosphate content in the soil increased by 59.32%. The content of extractable state Pb2 + and Cd2 + decreased by 65.06 and 71.26%, respectively. And the soil nutrient conditions were significantly improved. Synergistic remediation can significantly increase the diversity and abundance of soil microbial communities (p < 0.05). Janibacter, Lysobacter, Ornithinimicrobium, Bacillus, and Salinimicrobium were the main functional flora during soil remediation, with significant correlations for the promotion of Pb2 + and Cd2 + immobilization and the increase of available phosphate and organic matter. ZitB, czcD, zntA, and cmtR are the major heavy metal resistance genes and regulate metabolic pathways to make microbial community function more stable after soil remediation in phosphate mining wasteland.